“Encontré Algo Mejor” / “I Found Something Better”: Trans- Perspectives and Raising Critical Consciousness with Secondary Bilingual/Multilingual STEM Teachers - Solís, Jorge L.; Howard, Talia; Mosqueda, Eduardo; Bravo, Marco A. (International Journal of Multicultural Education, 2025)
This study presents findings from a professional development project that engaged secondary school in-service STEM teachers in transformative perspectives to make sense of theory, practice, and action in multilingual STEM classrooms. In particular, we examine how teachers engaged with translanguaging, transdisciplinarity, and transculturation in critical reflections and course discussions to promote critical consciousness. Findings reveal that trans- perspectives were interconnected and integral in promoting criticality and equity-minded STEM teaching in bilingual contexts. Teachers historicized personal experiences through translanguaged narratives; connected and integrated STEM language and content knowledge through transdisciplinary practices; and grappled with the role of culture in STEM learning through transcultural repositioning.